Super twisting sliding mode control for brushless doubly fed induction generator based on WECS, ISSN 0975-6809 - Moussa Oussama; Abdessemed Rachid; Benaggoune Said (International Journal of System Assurance Engineering and Management, 2019)
This paper deals with the robust power control of a grid-connected brushless doubly-fed induction generator (BDFIG) driven by the variable speed wind turbine. With the using of a super twisting algorithm which is a high-order sliding mode controller (HOSMC). This approach guarantees both the dynamic performance and the same robustness as traditional first order (SMC) algorithm and reduces the chattering phenomenon, which is the biggest disadvantage in the implementation of this technique. The developed algorithm relies on the decoupling control by implementing the strategy of oriented grid flux vector control. In order to enhance the desired performances, an attempt is made by controlling the generated stator active and reactive powers in a linear and decoupled manner to ensure the global asymptotical stability, HOSMC approach is implemented. Therefore, an optimal operation of the BDFIG in sub-synchronous operation is used in addition to the stator power flows where the stator power factor is kept in a unity. The suggested method is examined with the Matlab/Simulink software. The performances and the feasibility of the designed control are illustrated by simulation results.